Early metabolic profiling in the periparturient period reduces the occurrence of postparturient metabolic diseases in cows - Ahammed, Mustak; Nooruzzaman, Mohammed; Islam, Md Taohidul; Alam, Md Rafiqul; Chowdhury, Emdadul Haque (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: To study the impact of early metabolic profiling and intervention measures in the periparturient period on the occurrence of postparturient metabolic diseases in cows. Materials and Methods: Using a cohort of dairy cows from two selected areas of Bangladesh, we routinely tested the serum calcium level and ketone bodies in the urine at periparturient periods. In addition, milk samples were tested for the presence of mastitis at different stages of lactation. Animals showing reduced serum calcium levels, high ketone bodies in the urine or the presence of clinical and subclinical mastitis received appropriate therapeutic intervention immediately after detection. After the intervention, the number of animals that got sick with diseases or conditions like milk fever, ketosis, mastitis, and dystocia, which are caused by metabolic problems, was recorded. Results: In the periparturient period, most of the animals had lower serum calcium levels (8.13 ± 1.2 mg/dl), which were significantly increased by the following intervention (10.05 ± 1.4 mg/dl). On the other hand, there was a higher number of ketosis-affected animals (33.9%, 20/59) during the periparturient period, which decreased (18.6%, 11/59) during the postparturient period. Similarly, the number of mastitis-affected cows was also decreased in postparturient cows (30.9%, 13/42) than in periparturient cows (59.5%, 25/42), following improved hygienic measures. After early intervention, the number of study animals with metabolic diseases decreased from 51.7% before intervention to 15.3% after intervention. Conclusions: Early metabolic profiling significantly reduced the occurrence of metabolic diseases in cows. Therefore, we recommend regular metabolic profiling of dairy cows and receiving early intervention measures to reduce the occurrence of metabolic diseases on the farm. J. Adv. Vet. Anim. Res., 9(2): 295–300, June 2022 http://doi.org/10.5455/javar.2022.i596